The effect of nei-guan point acupressur massage on emesis gravidarum - Prasanti Adriani; Suryo Ediyono; Mariah Ulfah; Siti Haniyah (Universitas 'Aisyiyah Yogyakarta, 2022)
Excessive nausea and vomiting can threaten the health of pregnant women and fetuses, about 80% of pregnant women are treated for hyperemesis gravidarum. Nie-Guan point acupressure massage is a non-pharmacological treatment that can treat nausea and vomiting for pregnant women. The aim of this research to determine the effect of Nei-Guan point acupressure massage on emesis gravidarum. Design of this study was a quasi-experimental study with a nonequivalent control group design approach. Age, intervention and control were mostly at high risk 11 people (73%) and 10 people (67%). The most education is secondary in the intervention group 12 people (80%) and the control group 13 people (87%). Most of the respondents as IRT in the intervention group were 8 people (53%) and in the control group 10 people (67%). Pregnancy in the intervention and control groups was the same in primigravida 8 people (54%). The management of nausea and vomiting that is most often done is by giving warm and refreshing drinks, but not a few mothers also refuse, one non-pharmacological approach that can be given is acupressure (Grove et all, 2015). This study explains that giving acupressure point P6 (Nei-Guan) has an effect on emesis gravidarum.